KARAKTER MORFOLOGI UBI KAYU (Manihot esculenta Crantz) HIJAU DARI KABUPATEN PELALAWAN - Rini Restiani; Dewi Indriyani Roslim; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Many cassava varieties or genotypes have been grown or planted by farmer in Pelalawan, and one of them is cassava cv. Hijau. This study was aimed to identify morphological character of cassava cv. Hijau from Pelalawan. The cassava stems were obtained from Langgam, Kabupaten Pelalawan. The seven cassava stems were planted as replication. Morphological characters, including leaf shape, color of apical and fifth leaf, petiole color, stem color, stem diameter, flower, fruit, and tuber, were observed on 5 and 12 months after planted. Results showed that cassava cv. Hijau had lanceolate leaf with sharp tip, light-green apical leaf, and dark-green fifth leaf. The petiole was yellowish-green. The stem diameter was medium (12-25 mm) and the color stem was yellowish-green. The flower was monoecious. The fruit was rounded and jagged. The tuber shape was cylindrical and its color was white.